Keeping refugee children in school and out of work: Evidence from the world's largest humanitarian cash transfer program - Aysun Hızıroğlu Aygün; Murat G. Kirdar; Murat Koyuncu; Quentin Stoeffler (Koç University-TÜSIAD Economic Research Forum (ERF), 2021)
This paper investigates whether unconditional cash transfers can keep refugee children in school and out of work. We raise this question in the unique context of Turkey, which hosts the world's largest refugee population (including 3.6 million Syrians). Refugees in Turkey are supported by the world's largest cash transfer program for refugees, the Emergency Social Safety Net (ESSN). We exploit a program eligibility criterion to identify the causal impacts of the ESSN program using a regression discontinuity design. The results show a large effect on child labor and school enrollment among both male and female refugee children. Being a beneficiary household reduces the fraction of children working from 14.0 percent to 1.6 percent (a decrease of 88 percent) and the fraction of children aged 6-17 not in school from 36.2 to 13.7 percent (a reduction of 62 percent). By unpacking the mechanisms at play, we show that ESSN cash transfers become a significant part of a household's income, substantially alleviate extreme poverty, and reduce a family's need to resort to harmful coping strategies. Investigating the reasons for children not attending school, we find that the beneficiary households become more likely to send children to school because the cash transfer addresses both the opportunity cost and direct cost of schooling - although the former is more important. The findings have important implications for the design of policies aimed at supporting refugee children at scale.
Keywords: F22; I21; I28; I38; J21; O15; O22; 330; refugees; cash transfers; education; child labor; regression discontinuity design; program evaluation; Turkey